HOME GROWN SCHOOL FEEDING PROGRAMME AND POVERTY REDUCTION IN RIJAU LOCAL GOVERNMENT AREA NIGER STATE, 2017-2022 - Fidelis Achoba; Danlami Abdullahi Saliu (International Studies Journal)
The study examined the impact of a Home Grown School Feeding Program on poverty reduction in Rijau Local Government Area (HGSF). The implementation of the HGSF program in Rijau Local government was to achieve lots of objectives aside the reduction of poverty. The HGSF program was meant to increase the nutrition of school children, increase school attendance and enrollment, create job for villagers and increase local agricultural production. The study fund the HGSF program to have positive impact on the nutrition of children, school enrollment and attendance, job creation, crime prevention and on the whole reduced poverty in Rijau Local Government of Niger State.